2019
DOI: 10.1177/2168479018791133
|View full text |Cite
|
Sign up to set email alerts
|

Age-Appropriate Pediatric Dosage Forms in Japan: Insights into End-User Perceptions From an Observational Cross-Sectional Survey Assessing the Acceptability of Oral Formulation

Abstract: The difference in caregivers' perception of the acceptability of oral formulations between Japan and Europe was small. The powder form was found to be more acceptable in Japan. Further intervention studies are needed to assess the preferred pediatric formulation worldwide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…') by drug type and dosage the capsule in this survey based on available antivirals in market. The size of oral drugs is reportedly an important factor when choosing treatments for children [7,17,18], which is associated with higher preference for tablet in previous reports from Japan [18] and the United Kingdom [17]. Our survey results indicate that difficulty swallowing the drug was the most frequent reason children had trouble taking both capsules and tablets and the percentage was larger for capsules than for tablets (21.7% vs. 16.3%).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…') by drug type and dosage the capsule in this survey based on available antivirals in market. The size of oral drugs is reportedly an important factor when choosing treatments for children [7,17,18], which is associated with higher preference for tablet in previous reports from Japan [18] and the United Kingdom [17]. Our survey results indicate that difficulty swallowing the drug was the most frequent reason children had trouble taking both capsules and tablets and the percentage was larger for capsules than for tablets (21.7% vs. 16.3%).…”
Section: Discussionmentioning
confidence: 53%
“…Different preferences were observed among the oral drugs; capsules and dry syrup were less preferred, whereas tablets were preferred over inhalants. While the administration route, oral and inhalant, has been compared in a previous study for adults [5], the current study also looked at the type of formulation in addition to administration route, because formulation is considered an important factor affecting acceptability in pediatric patients [6,7,[16][17][18]. One of the reasons for the higher preference for tablets than capsules may be associated with its size, which was set smaller for the tablet than Fig.…”
Section: Discussionmentioning
confidence: 99%
“…In further study in Japan, it may be better to advise caregivers to administer multiple minitablets all at once. As reported by Saito et al [17], parents and nurses often dissolve or disperse powder formulations in water for children. Alessandrini et al also reported that liquid formulations were widely selected by children less than 12 years and granules were not appreciated, particularly by adolescents [18].…”
Section: Discussionmentioning
confidence: 99%
“…The pediatric population may also prefer nonsolid oral dosage forms for easier ingestion. 56 Liquid formulations allow more precise dosing to maximize efficacy and decrease AEs. Moreover, age-related health complications in the older patients, such as dysphagia, may require alternate or modified dosage forms.…”
Section: Safety Considerations/adverse Effectsmentioning
confidence: 99%